The Modus Operandi of Hydrogen Sulfide(H2S)-Dependent Protein Persulfidation in Higher Plants - Francisco J. Corpas; Salvador González-Gordo; María A. Muñoz-Vargas; Marta Rodríguez-Ruiz; José M. Palma (Antioxidants, 2021)
Protein persulfidation is a post-translational modification (PTM) mediated by hydrogen sulfide (H2S), which affects the thiol group of cysteine residues from target proteins and can have a positive, negative or zero impact on protein function. Due to advances in proteomic techniques, the number of potential protein targets identified in higher plants, which are affected by this PTM, has increased considerably. However, its precise impact on biological function needs to be evaluated at the experimental level in purified proteins in order to identify the specific cysteine(s) residue(s) affected. It also needs to be evaluated at the cellular redox level given the potential interactions among different oxidative post-translational modifications (oxiPTMs), such as S-nitrosation, glutathionylation, sulfenylation, S-cyanylation and S-acylation, which also affect thiol groups. This review aims to provide an updated and comprehensive overview of the important physiological role exerted by persulfidation in higher plants, which acts as a cellular mechanism of protein protection against irreversible oxidation.